Determining the Effect of Iron Deficiency Anemia on HbA1c Levels in Patients with Diabetes Mellitus - Smita Vasava; Roshni Sadaria (Research Developments in Medicine and Medical Science Vol. 5, 2023)
The present study will estimate HbAlC levels in iron-deficient anaemic individuals with fasting blood glucose levels less than 126 mg/dl. An indication of a patient’s glycemic status over the previous three months is haemoglobin A1C (HbA1c). When iron deficiency anaemia is present, HbA1C levels rise. A total of 50 patient of diabetes mellitus with iron deficiency anemia with controlled plasma glucose levels were taken as a cases and 50 iron-sufficient non-anemic healthy individuals were taken as a controls. Medical history was taken from all participant and data of HbA1c, ferritin, FBS, hemoglobin, peripheral smear examination, red cell indices were collected from laboratory. HbA1C level (6.90 ± 0.81%) were increased in iron-deficient individuals as compared to controls. In females, HbA1C (7.08 ± 0.78%) were more elevated than males. HbA1C concentration was significantly higher in iron deficient anemic individuals who had less than 126 fasting plasma glucose level. In the present study, HbA1C levels were demonstrated according to the age, sex and plasma glucose level. A positive correlation found between iron deficiency anemia and increased HbA1C levels, especially in the controlled diabetic women and individuals having FBS between 100-126 mg/dl. It is important to check for iron deficiency anaemia before changing a patient’s diabetes mellitus treatment plan. Study observations can be attributable to the fact that iron deficiency anemia should be considered before altering the treatment of diabetic patients.